Living in a Time of Madness: Last Days of Java's Last Prophetic Poet - Florida, Nancy K. (History and theory, 2019)
Shortly before his death in December 1873, the renowned Javanese court poet R. Ng. Ronggawarsita composed a short work of social criticism and Islamic ethics that is among the most celebrated of Javanese literary texts. Serat Kalatidha (The Time of Darkness) reflects upon the avenues that remain open to the ethical subject in what Ronggawarsita calls the “time of madness,” the time of darkness and error that marked his dismal present in high colonial Java. Most celebrated as a prophecy, the poem is, in part, a critical reworking of an early nineteenth-century prophetic reflection on the Javanese past. My article explores the troubled context in which the author wrote this twelve-stanza (108-line) poem and how its text forms both a critical commentary on the state of the poet's current-day society and a pensive reflection on the ethical imperatives of Islam. In the course of this exploration, I reveal how Ronggawarsita's poem forms a prophecy, not as a foretelling of an already determined future, but rather as a work that moves along prophetic time to provoke in his readers a productive intimacy with both pasts and futures.